The Dweller on the Threshold: Whiteness, the Family and the End of Classical Cinema - Conall Cash (Film-Philosophy)
Through a discussion of two key American films of the 1940s and 1950s – Alfred Hitchcock's Shadow of a Doubt (1943) and John Ford's The Searchers (1956) – this article situates the breakdown of classical cinema, or what Gilles Deleuze calls the “crisis of the action-image”, in relation to the critique of whiteness and the family. Focusing on the figure of the “dweller on the threshold” within these two films, the article shows how this individual's deprivation of action is tied to their status simultaneously as protective of and estranged from the white family. Once whiteness and the family become explicit objects of protection, the myth of their naturalness and goodness is rendered problematic, and in these films, the protector themselves must be excluded in order for the myth to function. Drawing on accounts of the invisibility and dehistoricisation entailed in whiteness in the work of Sara Ahmed, Jacques Derrida, Toni Morrison and Frank B. Wilderson III, the article considers how, in these films, the protection of the white family reveals its mythical status as an ideally ahistorical unit of civilisation. The very effort to protect this myth, these films show, amounts to its collapse. These films enact a deconstruction of the oppositions which constitute the civilisational myths that ground whiteness and return such myths to the moment of their historical institution. They reflect on the very process of erasure and forgetting that produces these myths, through a self-conscious interrogation of the cinematic process of the projection of images itself. Drawing on Deleuze's suggestion that modern cinema promises a new mode of belief in the world, the article argues that such a non-mythic belief can only be realised through an unmaking of whiteness, as a form of life which, being premised upon protection and immunity, denies life itself, and our living connection to the world.